Psychological profiles of resilience in extreme environments: Correlating measures of personality and coping and resilience - Van Wijk, Charles (Scientia Militaria - South African Journal of Military Studies, 2022)
The presence of psychological resilience appears to confer positive personal benefits, and may be particularly advantageous for individuals working in isolated, confined, and extreme environments. This study aimed to identify contextually adaptive ‘resilient’ personality and coping profiles in such contexts. This was done by correlating scores on measures of resilience with scores on measures of personality and coping, using specialists identified as good adaptors. As resilient profiles may differ across contexts, two highly specific samples were used, namely navy divers and submariners. This paper presents psychometric profiles of contemporary personality and coping styles. Then, using bivariate correlations, resilience-associated, context specific, diver and submariner personality and coping profiles were identified. Their resilient profiles appeared well suited to their respective environments. Some differences were noted between the typical personality descriptions and the resilient profiles identified, with three possible reasons forwarded to understand this. Firstly, there were some concerns regarding the validity of the measures in the local cultural context; secondly, context specific resilience may be expressed differently from resilience in general society; and thirdly, contemporary profiles of specialists may reflect current organisational processes in addition to psychological factors. In terms of practical application, while the identification of resilient profiles may also have value for selection purposes, it could be particularly useful for mission preparation, through the training of context-relevant coping skills.